ONE HEALTH APPROACH TO ANTIMICROBIAL RESISTANCE IN MASTITIS: EXPLORING SUSTAINABLE TREATMENT ALTERNATIVES - Uzoka, Ugonna Henry; Bolawa, Oluseun Peter; Olufemi, Abimbola Gabriel; Esama, Preye Francisca; Edward, Idopise Godwin; Isiaka, Amarachukwu Bernaldine (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Antimicrobial resistance (AMR) in bovine mastitis has become an increasing concern for public and veterinary health, compromising the effectiveness of conventional treatments and raising management costs. Mastitis is primarily caused by Staphylococcus aureus and Escherichia coli, pathogens that have shown increasing resistance to common antibiotics such as penicillin and tetracycline. The One Health approach, integrating human, animal, and environmental health sectors, emerges as an effective strategy to combat resistance and improve treatment efficacy. This study systematically reviewed articles published between 2020 and 2025, utilizing PubMed, BIREME and SciELO databases, aiming to assess how the One Health approach impacts AMR in mastitis and explore sustainable therapeutic alternatives. A total of 19 articles meeting the inclusion criteria were selected, addressing the prevalence of AMR in mastitis pathogens as well as the application of vaccines and phytotherapies as alternatives to antibiotic use. Results showed that resistance primarily increased due to excessive antibiotic use, while the One Health approach was found promising in controlling resistance by integrating veterinary, public health, and environmental practices. Additionally, sustainable alternatives such as vaccines and phytotherapies proved effective in reducing resistance without introducing new resistance issues. This study concludes that the implementation of the One Health approach, combined with sustainable alternatives, offers an effective model for controlling antimicrobial resistance in bovine mastitis. However, it is important to highlight the scarcity of in-depth studies on the long-term efficacy and viability of sustainable therapeutic alternatives. The lack of robust data limits the application of these solutions in the field and emphasizes the urgent need for new studies to confirm their effectiveness on a large scale. The implementation of public policies encouraging collaboration among human, animal, and environmental health sectors is also essential to optimize outcomes in managing antimicrobial resistance.